2014
DOI: 10.3168/jds.2014-8180
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding a low-phosphorus diet on leucocyte function in dairy cows

Abstract: Phosphorus depletion and hypophosphatemia have been described to interfere with immune function in rats and humans. In dairy cows, hypophosphatemia has been associated with muscle weakness and recumbency as well as with intravascular hemolysis resulting from increased osmotic fragility of erythrocytes, but so far, the influence of P depletion and hypophosphatemia on immune function has not been studied. Therefore, the aim of this study was to investigate whether P depletion and ensuing hypophosphatemia are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…In the case of beef cattle breeding, phosphorus content above 0.17% should suffice (Mc Dowell, 1996). When phosphorus content in feed is too low, there can be problems with animal health associated with the limited ability to move, osteopathic lesions, and with problems with reproduction (Eisenberg et al 2014). The problem of macro element deficiency in cattle eating feed from one source was emphasized particularly by Mc Dowell (1996) and McNamara et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of beef cattle breeding, phosphorus content above 0.17% should suffice (Mc Dowell, 1996). When phosphorus content in feed is too low, there can be problems with animal health associated with the limited ability to move, osteopathic lesions, and with problems with reproduction (Eisenberg et al 2014). The problem of macro element deficiency in cattle eating feed from one source was emphasized particularly by Mc Dowell (1996) and McNamara et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…One study conducted in non-periparturient dairy cows and feeding diets with varying amounts of P, covering a range at or above current recommendations for dietary P content for dairy cow rations, did not reveal an effect of the dietary P content on the innate or cell-mediated immune response (Mullarky et al, 2009). A second study conducted in mid-lactating dairy cows and feeding a markedly P-deficient diet reported a negative effect of dietary P deprivation on granulocyte survival but no negative effect on the phagocytic activity of viable granulocytes (Eisenberg et al, 2014).…”
Section: Effect Of Dietary Phosphorus Deprivation On Leukocyte Function In Transition Cowsmentioning
confidence: 90%
“…Leukocytes were isolated from EDTA blood under sterile conditions using osmotic lysis as described be-fore with slight modification (Eisenberg et al, 2014). Briefly, 18 mL of distilled water was added to 9 mL of EDTA blood and after 30 s iso-osmolarity was restored by adding 2 mL of 10× PBS (Lonza Group AG, Basel, Switzerland) to the sample.…”
Section: Leukocyte Isolation and Phenotypingmentioning
confidence: 99%
See 2 more Smart Citations